PERSEPSI MASYARAKAT TERHADAP JALUR EVAKUASI TSUNAMI DI NAGARI PAINAN KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Andre Ayadi; Deded Chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACT Andre Ayadi. COMMUNITY PERCEPTION OF THE TSUNAMI EVACUATION ROUTE IN NAGARI PAINAN DISTRICT IV JURAI, PESISIR SELATAN REGENCY. Thesis, Padang: Faculty of Social Sciences. Padang State University. 2021 This study examines: 1) public perception of tsunami evacuation routes in Nagari Painan 2) barriers to tsunami evacuation routes in Nagari Painan. This type of research is qualitative. Research informants are the Painan community. data collection techniques using interviews, observation, documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results of this study are: 1) The community already knows that Painan is prone to tsunamis, Painan already has tsunami evacuation facilities, evacuation routes are feasible, the community is assisted by local institutions to coordinate with each other, the capacity of evacuation routes is sufficient for the community, the equipment is adequate, People feel comfortable through the evacuation route. Distance The evacuation route is quite effective. 2) For obstacles on the evacuation route, according to the respondent there are no obstacles, but the respondent gives the view that if a tsunami occurs then do not use 4-wheeled vehicles because it will become an obstacle when evacuating.